Communicating risk in disaster risk management systems – experimental evidence of the perceived usefulness of risk descriptions. Issue 12 (2nd December 2017) - Lin, Lexin; Rivera, Claudia; Abrahamsson, Marcus; Tehler, Henrik
Abstract : Disaster risk management (DRM) requires the collaboration of a variety of stakeholders working in different sectors. They depend on each other to share risk information, and effective collaboration requires efficient communication. Clearly, the communication of risk descriptions is a key issue for the success of DRM activities. This study investigated the communication of risk-related information between DRM actors, and how to present such information in order to improve its usefulness as a basis for decision-making. Two experiments were conducted to investigate the issue. The first related to the type of hazard, while the second examined the presentation of likelihood and consequences. We addressed two research questions: Does the presentation of a risk description influence its perceived usefulness for decision - making in a DRM system? If so, which format is perceived as most useful? Our findings indicated that the type of hazard did not affect perceived usefulness to any significant extent. However, the presentation of likelihood and consequences did have a significant effect. These results indicate that the presentation of risk information greatly influences stakeholders' ability to make well-informed decisions. Specifically, quantitative scale and semi-quantitative ranking scale formats are perceived as most useful.